Strategi Pengembangan Pemasaran Sukuk Wakaf Ritel Indonesia - Reska Prasetya; Muhammad Zilal Hamzah; Nurwahidin; Fahruroji (Department of Islamic Economics, IPB University, 2021)
Waqf is an Islamic social financial instrument that plays an important role in development. In order to play an optimal role, waqf needs to be managed productively, including through the Retail Cash Waqf Linked Sukuk (CWLS) or Retail Sukuk Waqf, which is an innovation in developing cash waqf through placement on Government Islamic Securities. The presence of this program opens opportunities for safe, productive, optimal and rewarding cash waqf investment. However, the very low marketing results of Retail Sukuk Waqf compared to other retail Sukuk types indicate that there are problems in the marketing of this instrument. This study aims to proposed strategy for developing retail Sukuk Waqf marketing through an analysis of the strengths, weaknesses, opportunities and challenges of Retail Sukuk Waqf. The proposed strategy is to improve the marketing system by changing the sales scheme from offline to online, increasing the number of MIDIS, determining the appropriate issuance timing, increasing socialization and promotion, offering reasonable returns, and making variation tenor of Retail Sukuk Waqf to the shorter one. In addition, it also needs to be supported by efforts to increase transparency and accountability of nazhir to enhance the convenience of the community in making cash waqf.